2016
DOI: 10.5465/ambpp.2016.17681abstract
|View full text |Cite
|
Sign up to set email alerts
|

Do Friends Perform Better?: A Meta-Analytic Review of Friendship and Group Task Performance

Abstract: In the current paper, I develop and test a theoretical model aimed at understanding the relationship between friendship and group performance. Specifically, using data from 924 teams in 24 studies, I tested my hypothesized main effect, and key moderator analyses, for how working with friends, versus non-friends, would influence group task performance. Results show that friendship has a positive effect on group task performance (d=0.45). Furthermore, as expected this effect was moderated by task interdependence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…We did not expect the lack of influence of friendship on performance or joint attention, as prior work has demonstrated that friendship can facilitate performance in decision-making and motor tasks (e.g., Shah & Jehn, 1993). However, a recent meta-analytic review of the effect of friendship on team performance indicates that the positive relationship is mediated by the degree of task interdependence (Chung, 2015). This reinforces our interpretation that role differentiation played a key part in the development of team performance over time.…”
Section: Resultsmentioning
confidence: 96%
“…We did not expect the lack of influence of friendship on performance or joint attention, as prior work has demonstrated that friendship can facilitate performance in decision-making and motor tasks (e.g., Shah & Jehn, 1993). However, a recent meta-analytic review of the effect of friendship on team performance indicates that the positive relationship is mediated by the degree of task interdependence (Chung, 2015). This reinforces our interpretation that role differentiation played a key part in the development of team performance over time.…”
Section: Resultsmentioning
confidence: 96%